Serial relaying over gamma-gamma MIMO FSO links. (c2015) - Abdo, Alfred Youssef (2016)
Free Space Optical (FSO) channels with Multiple-Input Multiple-Output (MIMO) hops and serial relaying are studied under the e ects of Gamma-Gamma modeled atmospheric turbulence alone, and under the combined e ects of atmospheric turbulence, path loss and pointing er- rors. Asymptotic approximations and diversity orders are derived for both cases, and show the importance of proper aperture allocation for improving channels' performance. A recursive al- gorithm is proposed for optimally allocating apertures among hops for a serially-relayed MIMO FSO channel.